Supplementation with Gliricidia sepium and Leucaena leucocephala on voluntary food intake, digestibility, rumen fermentation and live weight of crossbred steers offered Zea mays stover - Abdulrazak, S.A.; Muinga, R.W.; Thorpe, W.R.; Orskov, E.R. (Elsevier, 1997)
Twenty intact and five fistulated crossbred steers were used in two experiments to examine the effect of supplementing maize stover with Gliricidia sepium or Leucaena leucocephala forage on intake, rumen fermentation, microbial protein supply and live weight changes. The basal diet plus 1 kg maize bran was offered alone or supplemented with 7.5, 15, 22.5 or 30 g DM/kg W to the quare root of 0.75 of gliricidia (experiment 1), and with either 15 or 30 g DM/kg W to the square root of 0.75 of gliricidia or leucaena forage (experiment 2). Supplementation increased total dry matter intake (TDMI) (P<0.001). DMI of stover was depressed (P<0.001) in experiment 1 from 2.1 to 1.3 kg/day, but increased at the lower levels of supplementation in experiment 2. Diet digestibility was only significantly increased in experiment 2. Supplementation increased the rumen ammonia from 53 to 106 mg/1 and from 31 to 111 mg/1 in experiment 1 and 2 respectively, and tended to improve the degradation characteristics of the basal diet. The efficiency of microbial N supply ranged between 21.0 and 27.7 g N/kg DOMR. The live weight gains from supplementation were greater, and the responses to gliricidia and leucaena did not differ significantly. It is concluded that the supplementation improved dry matter intake and liv-weight gains, and that Gliricidia sepium could be an alternative supplement to Leucaena leucocephala.